Double-sided pyramid texturing design to reduce the light escape of ultrathin crystalline silicon solar cells. (December 2019) - Guan, Li; Shen, Guangming; Liang, Yanan; Tan, Fengxue; Xu, Xiaofang; Tan, Xinyu; Li, Xu
Highlights: A comparative study on planar, front textured and double-sided textured structures. Double-sided textured structure remarkably suppresses light escape. Double-sided textured structure improve light absorption in long wavelength range. Double-sided textured structure show a small angle dependence. Abstract: Reducing the light absorption loss of ultrathin crystalline silicon (c-Si) solar cells is significant to achieve high photocurrent density and photoelectric conversion efficiency. Here, we designed and simulated ultrathin c-Si cells with front pyramids and double-sided pyramids. By adjusting the shape of pyramids, the maximum photocurrent densities reach 36.23 and 37.71 mA/cm 2 for the cells with front pyramids and double-sided pyramids, respectively. The reflectivity spectrum indicates that the double-sided pyramidal architecture remarkably suppresses light escape and then enhances the light absorption in long wavelength range, which makes the absorption approach the Yablonovitch limit. The calculated conversion efficiencies of planar, front and double-sided textured cells are 16.94%, 19.65% and 20.45% respectively. Additionally, the difference between randomly and periodically textured cells was investigated and the results show that although the randomly front pyramid texture has a better light absorption in the range of 900–1200 nm, the periodically double-sided pyramids texture exhibit almost the same light absorption in the whole range as the random one. Besides, the solar cells with double-sided pyramids show extremely small angular dependence of incident light. Thus, the double-sided light trapping structure designed in the present work provides an alternative pathway to improve the performance of ultrathin c-Si cells.